Evaluating Component Reliability in Safety Applications through Failure Analysis - Krishnamurthy, Kaushik; Venkata Ramanan, Lakshmi Narasimhan (My University, 2023)
This master’s thesis project addresses the critical role of component reliability in safety-critical system design, filling a substantial gap in existing research. It investigates a specific power distribution scenario presented by Volvo Cars, focusing on mitigating reverse current flow between two power supplies. Two design approaches are considered: one featuring an ISO 26262 non-compliant ideal-diode controller (LM74700) and the other incorporating a compliant alternative (STPM801). The study assesses the impact of component reliability through failure-analysis techniques, such as, failure modes, effects, and diagnostic analysis (FMEDA) and fault tree analysis (FTA), which calculates key safety hardware metrics per ISO 26262 — single point fault metric (SPFM), latent fault metric (LFM), and probabilistic metric for random hardware failure (PMHF). Findings indicated that the LM74700 resulted in a less reliable system in context of latent faults when compared with the system that used STPM801. While the non-compliant indicated to be less reliable due to lack of internal safety mechanisms, the rationale for choosing non-compliant components over compliant ones hinges on the specific application’s needs, considering complexity, ISO 26262 compliance, and design flexibility. The insights in this thesis project provide valuable guidance for engineers and stakeholders grappling with the intersection of safety and hardware design. Future research directions encompass comparisons between noncompliant designs with external safety mechanisms and practical verification tests to bridge theoretical and empirical outcomes, facilitating practical applications in safety engineering.
Keywords: ISO 26262; hardware circuit design; functional safety; safety analysis; failure analysis; SPFM; LFM; PMHF; FMEDA; FTA